Normal Exophthalmometry Values in Iranian Population: A Meta-analysis - Abbas Bagheri; Kourosh Shahraki; Amir Arabi; Mohsen Bahmani Kashkouli (Journal of Ophthalmic & Vision Research)
Abstract There are limited studies on the normal values of eye protrusion in Iran. Systematic efforts to provide acceptable normal exophthalmometry values for Iranian population are required for a proper approach to orbital diseases.English and Farsi language publications in PubMed, the ISI Web of Knowledge database, Iranian SID, and Iran Medex were searched using the following keywords: “proptosis”, “eye protrusion”, “exophthalmous”, “Hertel exophthalmometer” and “Iran”. Four articles from 1995 to 2010 were found and included in the meta-analysis. Statistical analysis was performed using the Metan command within Stata 15.0 software.It included 3,696 subjects in whom the average eye protrusion was 16.5 mm (95% CI: 15.1–17.8) in men and 16.2 mm (95% CI: 14.6–17.7) in women (P = 0.5). Mean left and right eye protrusion were 16.3 (95% CI: 14.7–18.1) and 16.4 mm (95% CI: 14.8–17.7), (P = 0.3), respectively. While Iranian teenagers (13–19 years old) showed a mean value of 17.1 mm (95% CI: 15.0–19.1), older age group ( ≥ 20 years) showed a lower mean eye protrusion of 16.3 mm (95% CI: 14.8–17.7). Considering the two standard deviations, the highest normal value of eye protrusion in Iranian population is 20.1 mm.In conclusion,Iranian normal eye protrusion values were higher than Asians and lower than Caucasians.